2022
DOI: 10.2196/34901
|View full text |Cite
|
Sign up to set email alerts
|

Motivations Toward Using Digital Health and Exploring the Possibility of Using Digital Health for Mental Health in Bangladesh University Students: Cross-sectional Questionnaire Study

Abstract: Background Digital health is efficacious for the management and prevention of mental health (MH) problems. It is particularly helpful for the young adult population, who appreciate the autonomy digital health provides, and in low-income countries, where the prevalence of MH problems is high but the supply of professionals trained in MH is low. Objective The objectives of this study are 2-fold: to determine whether university students in Bangladesh find … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Despite the lack of mental health professionals in Bangladesh, the most endorsed instrumental barrier for this sample was the cost of services in lieu of the availability of services. The high cost of mental health services may be why students of this sample were interested in using digital health for mental health support [34,35], as digital health provides a no to low-cost service for mental health promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of mental health professionals in Bangladesh, the most endorsed instrumental barrier for this sample was the cost of services in lieu of the availability of services. The high cost of mental health services may be why students of this sample were interested in using digital health for mental health support [34,35], as digital health provides a no to low-cost service for mental health promotion.…”
Section: Discussionmentioning
confidence: 99%
“…DHL encompasses searching for and finding health information from digital sources, comprehending and assessing it, and applying acquired knowledge to address health-specific questions and solve problems 31. It also encompasses skills and knowledge to interact productively with technology-enabled health tools 32 33. Other determinants that influence the utilisation of digital health applications include cultural and social factors,33–35 motivation and interest,32 33 36 37 and the accessibility and availability of technology 38–40.…”
Section: Introductionmentioning
confidence: 99%
“…It also encompasses skills and knowledge to interact productively with technology-enabled health tools 32 33. Other determinants that influence the utilisation of digital health applications include cultural and social factors,33–35 motivation and interest,32 33 36 37 and the accessibility and availability of technology 38–40. Subsequently, there is evidence of a relationship between DHL and adherence to digital health interventions 41 42…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages of mHealth are convenience, ease, cost-effectiveness, scalability, personalization, and “the ability to send time-sensitive messages with an ‘always on’ device” (Whittaker et al, 2016 ). In a sample of university students in Bangladesh, one study found that 26% (n = 82/311) of the sample currently use digital health for mental health promotion (Sifat, Saperstein, et al, 2022 ). The same study found that the majority of the sample (76.3%) reported that they were either somewhat or extremely likely to use an app for self-paced mindfulness or non-clinical practices to better their mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Further, mHealth can reach populations who would otherwise not engage with traditional health services (Hamine et al, 2015 ). One study found that higher non-stigma-related barriers to utilizing mental health care (such as not having transportation to access a mental health clinic) were significantly associated with using digital health for mental health Sifat, Saperstein, etal., ( 2022 ). It can also tackle social stigma, as accessing an app on a mobile phone can be done privately without fear of others watching.…”
Section: Introductionmentioning
confidence: 99%